2016
DOI: 10.1177/1460408616677562
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hospital and emergency department management of pelvic fractures and major trauma centre status: Has practice changed?

Abstract: Introduction: Pelvic fractures are indicative of high-energy injuries and carry a significant morbidity and mortality and pelvic binders are used to stabilise them in both the pre-hospital and emergency department setting. Our unit gained major trauma centre status in April 2012 as part of a national programme to centralise trauma care and improve outcomes. This study investigated whether major trauma centre status led to a change in workload and clinical practice at our centre. Methods: A retrospective analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Several studies have demonstrated ineffective use of pelvic binders in reducing fractures and promoting clot formation, due to poor accuracy of placement ( Barnes et al, 2017 ; Bonner et al, 2011 ; Henning et al, 2018 ). Data from this pilot study support the findings of existing research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated ineffective use of pelvic binders in reducing fractures and promoting clot formation, due to poor accuracy of placement ( Barnes et al, 2017 ; Bonner et al, 2011 ; Henning et al, 2018 ). Data from this pilot study support the findings of existing research.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research has identified poor accuracy of pelvic binder placement among patients attending hospital with suspected pelvic injuries ( Barnes et al, 2017 ; Bonner et al, 2011 ; Henning et al, 2018 ). There has been little research focusing solely on paramedic-led care, despite recommendations ( Barnes et al, 2017 ), while studies about pelvic binder use in UK HEMS relate to physician-led treatment ( Browne & Corfield, 2016 ; Yong et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelvic fractures can be classi ed according to the anatomical location or the mechanism of injury [3] and occur in 8% of major trauma patients and 15.7% of patients with an injury severity score > 15 [4]. These injuries can cause signi cant haemorrhage, with an overall mortality of 14-18% [4] which, in patients with unstable fractures can reach 40-42% [4,5] and 40-60% when associated with ring disruption and shock [6]. It is worth noting that in the recent years there has been an increase in the survival rate after pelvic fractures [7].…”
Section: Introductionmentioning
confidence: 99%